Comparative particulate characteristics of hydrogen, CNG, HCNG, gasoline and diesel fueled engines. (1st December 2016) - Singh, Akhilendra Pratap; Pal, Anuj; Agarwal, Avinash Kumar
Highlights: Diesel exhaust contains higher number of accumulation mode particles. PM from hydrogen, CNG and HCNG originated mainly from lubricating oil pyrolysis. Hydrogen emitted lowest particle numbers and lowest particle mass amongst test fuels. CMDs of hydrogen, CNG, HCNG and gasoline particulate were smaller than mineral diesel. Hydrogen enrichment of CNG led to improvement in total particle mass. Abstract: The present experimental investigations have been carried out to compare particulate emission characteristics of mineral diesel, gasoline, CNG, HCNG and hydrogen fueled engines. Experiments were performed in two identical constant speed engines, which were suitably modified to adapt to specific fuel properties (SI and CI engines). For each test fuel, particle number-size distributions, surface area-size distribution and mass-size distributions were determined at five engine loads ranging from no load to full load. These distributions are helpful in assessment of possible toxicity and atmospheric retention time of these toxic particulate. No visible tail-pipe particle emissions were observed from gasoline, CNG, HCNG and hydrogen. However, particulate number concentrations from these test fuels were significant compared to baseline mineral diesel, particularly for the nucleation mode (Dp < 50 nm) particles. Mineral diesel emitted significantly higher number of accumulation mode (Dp < 1000 nm) particles compared to other test fuels. Average particle size emitted in the gasoline, CNG, HCNG and hydrogen exhausts were much smaller compared to mineral diesel, under similar engine operating conditions. Particle surface area-size distribution showed that mineral diesel exhaust particles have relatively higher surface area in the accumulation mode whereas surface areas of particles from gasoline, CNG, HCNG and hydrogen were higher in the nucleation mode. Particle mass-size distribution of these test fuels indicated that particulate emitted from gaseous fuels cannot be neglected. Compared to mineral diesel, particulate mass contributed by all other test fuels were significant. Mass of nano-particles (Dp < 10 nm) emitted from gasoline, CNG and HCNG were slightly higher compared to mineral diesel. Thus partuculate emitted from gasoline, CNG, HCNG and hydrogen engines cannot be neglected because of their higher number concentrations in nucleation mode size range and particulate mass in both nucleation as well as accumulation mode size ranges.